Divergent Environmental Niches and Climate Vulnerabilities of Jonah Crab ( Cancer borealis ) and Atlantic Rock Crab ( Cancer irroratus ) - Everett J. Rzeszowski; Ruby Krasnow; Damian C. Brady (Fisheries Oceanography, 2026)
Jonah crab and Atlantic rock crab in the United States are currently assessed by National Oceanic and Atmospheric Administration climate change vulnerability assessments under the category Cancer crabs due to a dearth of species‐specific information across the attributes assessed. These species are frequently bycatch in the American lobster fishery and have low landed volume in comparison to larger Northeast US commercial fisheries. Here, we developed species distribution models using abundance, bottom temperature, and bottom salinity from Northeast Fishery Science Center Bottom Trawl data and calculated species‐specific environmental suitability indices. We used interpolated data to hindcast (1992–2024) environmental suitability in the five Jonah crab stocks for each species. Then, using similar methods, environmental suitability was forecasted from bottom temperature and bottom salinity conditions from 2075 to 2094 under RCP 8.5 climate conditions. This analysis found that Jonah crab occupies a narrow, stable niche, with optimal temperatures of 9°C–12°C in both seasons and habitat 150–350 m deeper than Atlantic rock crab, while Atlantic rock crab tolerates far larger swings, with the OSNE stock shifting optimal temperature by 11°C (5°C to 16°C) and salinity by 7 units between spring and fall. By identifying these differences, we show that Jonah crab's narrower thermal and salinity tolerance likely makes it more sensitive to climate change than the broadly tolerant Atlantic rock crab, refining species‐specific inputs for climate change vulnerability assessments and each species' potential as a long‐term fishery target.

Making the Most of Available Data: A Case Study of Converging Analyses to Model an Emerging Fishery for Jonah Crab ( Cancer borealis ) - Ruby Krasnow; Les Kaufman; Ethan Deyle (Fish and Fisheries, 2025)
Targeted fishing of Jonah crabs ( Cancer borealis ) has greatly intensified in recent decades as lobster populations have declined, forcing fishermen to shift their focus to Jonah and other crab species. Effective management of this developing fishery is limited, however, by a lack of information on their life history traits, abundance and distribution. The long‐term sustainability of the fishery depends upon near‐term efforts to maximise the value of existing data sources to assess species abundance and inform management. We applied three distinct modelling approaches—traditional linear regression, generalised additive models and empirical dynamic modelling—to data from the Maine–New Hampshire Inshore Trawl Survey to validate hypotheses about Jonah crab distribution and migration earlier derived from interviews with fishermen. There was strong agreement between the information reported by fishermen and the survey data, including depth preferences, seasonal inshore–offshore movements and sex‐specific migration patterns. This study demonstrates that rather than simply deploying a multi‐modal approach with model selection or averaging, employing a complement of statistical methods convergently and interfacing with engaged social science can better capitalise on limited fishery‐independent data to support the development of sustainable management frameworks for emerging fisheries.